Electromagnetic Radiation Force of Vortex Electromagnetic wave exerted on a perfect electromagnetic conductor (PEMC) Sphere - Muhammad Arfan; Abdul Ghaffar; Majeed. A. S. Alkanhal; Yasin Khan; Ali. H. Alqahtani; Sajjad Ur Rehman (Kuwait Journal of Science)
In this manuscript, the electromagnetic (EM) radiation force (RF) exerted on a PEMC sphere by a vortex electromagnetic (VEM) wave with spiral phase distribution had been investigated. The analytical formulation of EM fields is being done in the framework of Mie theory, while the field expressions are being modeled considering the features of VEM waves for PEMC sphere. Initially, the incident field coefficients are evaluated using definite integrals. The scattering coefficients are then determined by imposing boundary conditions at the surface of PEMC sphere i.e., at , leading to a linear system of equations computed via solving matrix. So, a lengthy calculation yields undetermined scattered field coefficients relative to incident field coefficients. The cross-section factors i.e., scattering cross section and extinction cross section  have been computed. The influence of sphere size parameter ( ) and beam waist radius  versus scattering angle ( ) for the RF along with scattering cross section  has been numerically analyzed. As no loss of energy occurs inside PEMC sphere so , by virtue of energy conservation principle then, . Under specific condition, we implemented present results on scattering cross section  towards light without OAM i.e.,  and plane wave for PEMC sphere. The research work has potential applications towards particle manipulation, optical technology, and optical tweezers.